12-month clinical outcomes of combined phacoemulsification and ab interno trabeculectomy for open-angle glaucoma in the United Kingdom. - Ejaz Ansari (Public Library of Science (PLoS), 2021)
Background/objectives To describe intraocular pressure (IOP) and ocular hypotensive medication outcomes of combined phacoemulsification and ab interno trabeculectomy with the Kahook Dual Blade (KDB; New World Medical, Inc, Rancho Cucamonga, CA) in adults with cataract and open-angle glaucoma (OAG). Subjects/methods Retrospective chart review of existing medical records. Data collected included intraocular pressure (IOP) and IOP-lowering medication use preoperatively and through up to 24 months postoperatively. Paired t-tests were utilized to compare preoperative to postoperative mean IOP and mean medications used. Results Data from 32 eyes of 26 subjects were analyzed. Subjects were predominantly Caucasian (25/26) had mean (standard error) age of 79.3 (1.2) years, and eyes had moderate-advanced OAG (mean visual field mean deviation -8.3 [1.3] dB). Mean IOP was 19.8 (0.8) mmHg at baseline and 15.5 (0.6) mmHg (p<0.0001) after mean follow-up of 11.5 (1.0) months; IOP reductions of ≥20% were achieved in 20/32 eyes (62.5%). Mean medication use declined from 2.4 (0.2) medications per eye at baseline to 0.5 (0.2) at last follow-up (p<0.0001); 23/32 eyes (71.9%) were medication-free at last follow-up. No vision-threatening complications were observed. Conclusions Combined phacoemulsification and ab interno trabeculectomy with the KDB safely provided mean IOP reductions of 21.7% and mean IOP medication reductions of 83% after mean follow-up of 12 months in eyes with moderate to advanced OAG. This procedure provides medication-independence in most eyes with statistically and clinically significant IOP reductions.